Damage stability of small vessel - Setyawan, Dony (2006)
The survivability of a vessel is related to intact and damage stability requirements. However, intact ship survivability has received more attention than damage ship survivability. This study seeks to emphasise in damage stability for the reason, the safety of passenger vessels has always been the prime concern of regulatory bodies. There are various ways of assessing the damage stability such as deterministic, probabilistic and real time simulation approaches. The purpose of this study is to further develop a ship stability program using MATLAB based on real time simulation of the dynamic behaviour of the damaged vessel in wave conditions. The mathematical model comprises six degrees of freedom motions in beam seas whilst taking into consideration progressive flooding as well as water accumulation. The ‘Sarawak Fast Ferry’ was chosen for parametric study for the application of the developed Damage Stability Program. Damage stability experiment was carried out to validate the simulation program. The experiment was conducted using image processing technique. Experimental results have shown good correlation to the results of simulation. The result of the study also indicated that wave height and loading conditions are the main parameters influencing ship’s stability in damage condition. The critical KG for Sarawak Fast Ferry was found to be 1.3 m and the vessel only can survive with wave height until 0.2 m. The safety KG was found to be 1.1 m since the vessel can survive with wave height 0.5m. On the basis of the results, suggestions are made to improve the damage survivability of the vessel.